1992
DOI: 10.1111/j.1432-1033.1992.tb16584.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of racemization of amino acids by aspartate aminotransferase

Abstract: Aspartate aininotransferase (mitochondrial isoenzyme from chicken) has been found to racemize very slowly dicarboxylic amino acid substrates in the presence of their cognate 0x0 acids [Kochhar, S. & Christen, P. (1988) Eur. J . Biochern. 175, 433-4381. Tyrosine, phenylalanine and alanine are racemized at the same rate although they undergo the transamination reaction 3-5 orders of magnitude more slowly than the dicarboxylic substrates. Similarly, the truncated enzyme aspartate aminotransferase-(27/32 -410) cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 20 publications
2
32
0
Order By: Relevance
“…In a genomic sequence analysis, we were unable to find candidate mammalian DR genes based on homology to serine racemase or bacterial aspartate racemases, which are either PLP-independent or PLP-dependent enzymes (14,15). Vacca and coworkers (16)(17)(18) demonstrated that glutamate-oxalacetate transaminase (GOT) can generate small amounts of D-aspartate in the process of transaminating Laspartate to L-glutamate, and that formation of D-aspartate is augmented in GOT mutants, wherein histidine replaces tryptophan-140 and lysine replaces arginine-292. Tryptophan-140 normally prevents access of a proton donor, such as a water molecule, which can effectuate racemization (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In a genomic sequence analysis, we were unable to find candidate mammalian DR genes based on homology to serine racemase or bacterial aspartate racemases, which are either PLP-independent or PLP-dependent enzymes (14,15). Vacca and coworkers (16)(17)(18) demonstrated that glutamate-oxalacetate transaminase (GOT) can generate small amounts of D-aspartate in the process of transaminating Laspartate to L-glutamate, and that formation of D-aspartate is augmented in GOT mutants, wherein histidine replaces tryptophan-140 and lysine replaces arginine-292. Tryptophan-140 normally prevents access of a proton donor, such as a water molecule, which can effectuate racemization (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…An increase in the rate of racemization is only observed with alanine as substrate. Apparently, the protonating water molecule (Kochhar and Christen, 1992) finds easier access to the re side of Ca in the case of alanine than of dicarboxylic or aromatic substrates. The side chain of alanine binds less tightly and fails to induce the movement of the small domain that closes the active-site cleft (Kirsch et al, 1984;Sandmeier, E., unpublished).…”
Section: Discussionmentioning
confidence: 99%
“…This slow side reaction occurs only once during lo7 transamination cycles (chicken mitochondrial AspAT) and is due to the reprotonation of the coenzyme-substrate adduct at Ca from the re instead of the si side (Kochhar and Christen, 1988). No ionizable groups are located at the re side; a transient water molecule appears to be responsible for the protonation at Ca from this side, its diffusion into the active-site pocket being the rate-limiting step of AspAT-catalyzed racemization (Kochhar and Christen, 1992).…”
mentioning
confidence: 99%
“…The kit provides a rapid, simple, sensitive, and reliable test suitable for high throughput activity assay of ALT with a detection limit of 10mU per well [14].…”
Section: Methods Used For Ast Determinationmentioning
confidence: 99%